AIAA Infotech@Aerospace Conference 2009
DOI: 10.2514/6.2009-2056
|View full text |Cite
|
Sign up to set email alerts
|

Flight Test Comparison of Different Adaptive Augmentations of Fault Tolerant Control Laws for a Modified F-15 Aircraft

Abstract: This report describes the improvements and enhancements to a neural network-based approach for directly adapting to aerodynamic changes resulting from damage or failures. This research is a follow-on effort to flight tests performed on the NASA F-15 aircraft as part of the Intelligent Flight Control System research effort. Previous flight test results demonstrated the potential for performance improvement under destabilizing damage conditions. Little or no improvement was provided under simulated control surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The evaluation was based on performance measurements and pilot ratings. As reported in [26,27], for structural damages, NN augmentation was generally found to provide significant improvements in overall pitch performance. However, control surface faults led to mixed results from slight improvements in pitch rate response to a propensity for roll pilot-induced oscillation.…”
Section: Intelligent Control Systemssupporting
confidence: 56%
See 2 more Smart Citations
“…The evaluation was based on performance measurements and pilot ratings. As reported in [26,27], for structural damages, NN augmentation was generally found to provide significant improvements in overall pitch performance. However, control surface faults led to mixed results from slight improvements in pitch rate response to a propensity for roll pilot-induced oscillation.…”
Section: Intelligent Control Systemssupporting
confidence: 56%
“…The utilized modifications included the use of alternate NN inputs in the de-signed framework which can satisfactorily tackle high-correlation and high-gain problems in the basic design, the adoption of a weight decay term (in updating the NN weights) to avoid the overfitting problem, and using scalar dead-zones in adaptation laws for simplicity. The results obtained by the modified control scheme in 2009 indicated a significant improvement over the basic design [27].…”
Section: Intelligent Control Systemsmentioning
confidence: 93%
See 1 more Smart Citation
“…Examples that do exist include the first flight tests of a model reference adaptive system on the F-94A aircraft (Lockheed Martin, Bethesda, Maryland), 1 an experimental adaptive flight control system evaluated on the F-94C aircraft (Lockheed Martin, Bethesda, Maryland), 2 the implementation of an adaptive flight control system on the X-15 aircraft (North American Aviation, Inc., Downy, California), 3,4 testing of an indirect-adaptive self designing controller (SDC) on the F-16 VISTA (General Dynamics, now Lockheed Martin, Bethesda, Maryland) 5 and the intelligent flight control system (IFCS) research on the highly-modified NASA F-15 aircraft (McDonnell Douglas, now The Boeing Company). 6,7 By the mid-2000s, experiments such as SDC and IFCS had demonstrated that adaptive flight controls can be an effective technology for improving aircraft safety in the event of failures or damage. However, the nonlinear, timevarying nature of adaptive systems continues to challenge traditional methods of verification and validation of safety-critical flight control systems.…”
Section: Introductionmentioning
confidence: 99%